Concealed costs: Illicit economies and the erosion of the local tax base in Colombia - Patricia Justino; Santiago Tobón; Martín Vanegas-Arias; Juan F. Vargas (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2024)
Tax revenues are fundamental to state-building and development, particularly in the aftermath of conflict. Through the lens of the recent post-conflict experience of Colombia, this paper explores the challenges of increasing tax revenues amid violence and illicit economic activities. We study four factors that the literature has identified as key determinants of a country's local fiscal capacity: early land conflicts; historical political violence; recent political violence; and the prevalence of illegal economies. We find that municipalities exposed to these factors feature lower tax revenues, with illicit crops being the most important predictor of poor tax performance. As different types of taxes are similarly correlated with the prevalence of illicit crops, we posit that illegal economic activities likely cause a comprehensive erosion of local fiscal capacity. Our findings contribute to understanding how illegal economic activities crowd out the local tax base in postconflict environments. Although the evidence offered in this paper is descriptive and does not establish causality, it highlights suggestive research avenues regarding the relationship between violence, illicit economies, and state capacity.
Keywords: D74; H71; O10; 330; taxation; conflict; violence; Colombia